RANCANG BANGUN SISTEM INFORMASI BERBASIS WEB DI PESANTREN INTERNASIONAL KH. MAS MANSUR UNIVERSITAS MUHAMMADIYAH - Muhammad Naufal Arlyanda; Tata Sutabri (CV. ADIBA AISHA AMIRA, 2023)
A planned web-based information system for KH. Mas Mansur at Muhammadiyah University aims to increase the efficiency and effectiveness of managing Islamic boarding schools' data and information. This system is designed to be accessed by users via the internet, both via desktop computers and mobile devices. The features that this information system will have include registration of new students, management of student and staff data, class schedules, announcements, activity schedules, and also a financial management system. In addition, this system is also equipped with a monitoring feature for the presence of students, as well as a health monitoring system for students. This information system was built using the latest technology with the PHP programming language and MySQL database. The system interface is designed with a user-friendly appearance and is easy for users to use. This system is also equipped with strong data security features, so that Islamic boarding school data and information are kept confidential. With this web-based information system, pesantren management can become more integrated and structured, so that pesantren can be more efficient and effective in managing pesantren data and information.